A construção histórica e política do professor/a leigo/a no brasil : um estudo de caso sobre o PROFORMAÇÃO - Aguiar, Ranieri Roberth Silva de (2007)
The present work shows the historical and political formation of teachers without formal education in an analytic and descriptive way, based on a case study research about "PROFORMAÇÃO" (Programa de Formação de Professores/as em Exercício) created by the Education and Culture Ministry, in partnership with State and Municipal governments. Fifty teachers from the municipalities of Luziânia and Cristalina. State of Goiás, graduated in 2002, were interviewed for this research. The answered questionnaires were processed by the Statistical Package for the Social Science. The research consisted of four parts. The first part showed an historical and political view on the formally unlearned teachers in Brazil, their origins and permanence in the Public Learning System and also on the geographic region where the unlearned teachers are concentrated. The second part analyzed, based on a general guide, the "PROFORMAÇÃO", its syllabus, operational system and some important aspects of the distance learning used for the teacher s formation. The third part presents the sample population interviewed. The fourth part demonstrates that PROFORMAÇÂO has problems in it's structural organization and needs adjustments concerning the admission of teachers with different knowledge levels for an equal level of teachers' formation. Finally, some suggestions to modify the program are made.